Unraveling Dowling–Degos Disease: A Rare Skin Disorder - Mahesh Mathur; Neha Thakur; Supriya Paudel; Sambidha Karki; Sandhya Regmi; Nabita Bhattarai (Clinical Case Reports, 2025)
ABSTRACT Dowling–Degos disease (DDD) is a rare genodermatosis characterized by brown to black macules distributed symmetrically in the axilla, groin, elbow, face, neck, and trunk. It is more common in women, usually after puberty. The main pathogenesis behind DDD is a mutation in the keratin 5 gene. Here, we present a case of 51‐year‐old female presenting as asymptomatic brownish‐black lesions arranged in a reticular pattern involving flexural sites. The clinical and histopathological findings are consistent with DDD. Her mother, brother, son, and daughter also had similar lesions. The patient was counseled about the prognosis and treatment options of the disease.